2008
DOI: 10.1021/es702160d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Asian and Western United States Urban Areas and Fires on the Atmospheric Transport of Polycyclic Aromatic Hydrocarbons, Polychlorinated Biphenyls, and Fluorotelomer Alcohols in the Western United States

Abstract: Atmospheric measurements of semivolatile organic compounds (SOCs) were made at Mt. Bachelor Observatory (MBO), located in Oregon’s Cascade Range, to understand the trans-Pacific and regional transport of SOCs from urban areas. High volume air sampling (~644 m3 for 24 hour periods) of both the gas and particulate phases was conducted from the 19th of April 2004 to the 13th of May 2006 (n=69); including NASA’s INTEX-B campaign in spring 2006 (n= 34 of 69). Air mass back trajectories were calculated and used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 28 publications
6
107
1
Order By: Relevance
“…5, Bottom). For example, BaP emitted from East Asia travels thousands of miles over the Pacific Ocean, reaching the west coast of the United States, consistent with previous observational studies that identified trans-Pacific atmospheric transport of PAHs (34)(35)(36). Similarly, BaP emitted from Western Europe travels to the east, and BaP emitted from South Africa travels over the South Atlantic Ocean, reaching South America.…”
Section: Resultssupporting
confidence: 87%
“…5, Bottom). For example, BaP emitted from East Asia travels thousands of miles over the Pacific Ocean, reaching the west coast of the United States, consistent with previous observational studies that identified trans-Pacific atmospheric transport of PAHs (34)(35)(36). Similarly, BaP emitted from Western Europe travels to the east, and BaP emitted from South Africa travels over the South Atlantic Ocean, reaching South America.…”
Section: Resultssupporting
confidence: 87%
“…Therefore the burning-related volatilization of historical residues of a-HCH and DDTs in spring could be another potential factor influencing atmospheric concentrations of the two compounds, which was also suggested in another report. 31 On the other hand, the mean g-HCH air concentration was 130 AE 150 pg m À3 , considerably higher than data reported elsewhere 13,14 but similar to levels measured at Waliguan Baseline Observatory. 10 The concentration reached a maximum during winter, especially in 2006 (Fig.…”
Section: Concentrations and Temporal Variationsupporting
confidence: 66%
“…Qomolangma,8,844.3 m a.s.l) and vast remote areas (e.g., the Qinghai-Tibetan Plateau), which indicated the national wide pollution of PAHs in China (Tao et al 2011;Wang et al 2007). In addition to local and national influence across China, PAH pollution can also influence the neighbor countries and regions through long-range atmospheric transport (Inomata et al 2012;Lang et al 2008;Primbs et al 2008). …”
Section: Introductionmentioning
confidence: 99%